2006
DOI: 10.1074/jbc.m601042200
|View full text |Cite
|
Sign up to set email alerts
|

The Calmodulin-binding Site of Sphingosine Kinase and Its Role in Agonist-dependent Translocation of Sphingosine Kinase 1 to the Plasma Membrane

Abstract: Sphingosine kinases catalyze the formation of sphingosine 1-phosphate, a bioactive lipid involved in many aspects of cellular regulation, including the fundamental biological processes of cell growth and survival. A diverse range of cell agonists induce activation of human sphingosine kinase 1 (hSK1) and, commonly, its translocation to the plasma membrane. Although the activation of hSK1 in response to at least some agonists occurs directly via its phosphorylation at Ser 225 by ERK1/2, many aspects governing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 53 publications
(71 reference statements)
1
65
0
Order By: Relevance
“…We suspect that the action of these calmodulin inhibitors on membranes could be responsible for a significant fraction of their many observed effects on cells. To cite just one example of a peripheral protein, Young et al (68) showed that 50 M W-7 prevents the binding of sphingosine kinase to the plasma membrane and reasonably attributed this effect to W-7 inhibiting Ca 2ϩ /CaM; recent mutation experiments appear to support this interpretation (69). Our results, however, suggest that this effect could equally well be due to W-7 reducing the surface potential of the plasma membrane, particularly because acidic lipids appear to mediate the membrane association of sphingosine kinase (70).…”
Section: Discussionmentioning
confidence: 90%
“…We suspect that the action of these calmodulin inhibitors on membranes could be responsible for a significant fraction of their many observed effects on cells. To cite just one example of a peripheral protein, Young et al (68) showed that 50 M W-7 prevents the binding of sphingosine kinase to the plasma membrane and reasonably attributed this effect to W-7 inhibiting Ca 2ϩ /CaM; recent mutation experiments appear to support this interpretation (69). Our results, however, suggest that this effect could equally well be due to W-7 reducing the surface potential of the plasma membrane, particularly because acidic lipids appear to mediate the membrane association of sphingosine kinase (70).…”
Section: Discussionmentioning
confidence: 90%
“…Indeed, Pitson et al (15) have shown that SphK1 is phosphorylated on Ser225 (human SphK1) by ERK1/2, which is necessary for its activation and translocation to the plasma membrane, perhaps by exposing a putative binding site for the membrane lipid phosphatidylserine (16). Subsequently, SphK1 was found to have a calmodulin binding site between residues 191-206, which was necessary for agonist-induced translocation to the plasma membrane but not required for activation (17). Recently, it was shown that protein phosphatase 2A negatively correlated with Ser225 phosphorylation and SphK1 membrane localization, suggesting that it may regulate SphK1 translocation (18).…”
Section: Activation Of Sphksmentioning
confidence: 99%
“…The latest data reported by Takasugi et al [52] indicated that the S1P pool synthesized by Sphk2 regulates β-amyloid (Aβ) precursor protein (APP) cleaving enzyme 1 (BACE1) activity and the Aβ level. Sphk1 resides predominantly in the cytosol and is translocated to the plasma membrane followed by ERK1/2-mediated phosphorylation [39,45,47]. Sphk1 is well known to synthesize the S1P pool, which exerts pro-survival effects within the cells.…”
Section: Introductionmentioning
confidence: 99%